2003
DOI: 10.1021/ja030297b
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Strategy for the Preparation of Cyclic Peptide Mimetics Based on SET-Promoted Photocyclization Processes

Abstract: A novel method for the synthesis of cyclic peptide analogues has been developed. The general approach relies on the use of SET-promoted photocyclization reactions of peptides that contain N-terminal phthalimides as light absorbing electron acceptor moieties and C-terminal alpha-amidosilane or alpha-amidocarboxylate centers. Prototypical substrates are prepared by coupling preformed peptides with the acid chloride of N-phthalimidoglycine. Irradiation of these substrates results in the generation of cyclic pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 23 publications
2
57
0
Order By: Relevance
“…hn (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Interestingly, compact flow reactors have been applied to prepare hundred of grams of bicyclic azepines using this photochemical strategy [78].…”
Section: Ring Contraction and Ring Enlargementmentioning
confidence: 99%
See 1 more Smart Citation
“…hn (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Interestingly, compact flow reactors have been applied to prepare hundred of grams of bicyclic azepines using this photochemical strategy [78].…”
Section: Ring Contraction and Ring Enlargementmentioning
confidence: 99%
“…N-Phthalimide-linked peptides that contain C-terminal a-amidotrimethylsilyl groups undergo macrocyclization reactions via sequential single-electron transfer processes [11,12]. Thus, electron transfer from the neighboring amide to the excited phthalimide chromophore leads to an amide radical cation.…”
mentioning
confidence: 99%
“…7 Synthetic approaches for the preparation of lariat crown ether have traditionally depended on ground state thermal polar cyclization reactions that require low concentrations of reactants to minimize competing polymerization processes. In previous studies aimed at the preparation of diverse types of macrocyclic poly-ethers, -thioethers, 8 and -peptides, 10 bis- 9 , and lariat 4c,4d,11a crown ethers we have developed protocols for promoting efficient single electron transfer (SET)-promoted photocylization reactions 11 of acceptor-polydonor substrates that proceed via sequential SET-desilylation mechanistic pathways (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Numerous examples of SET-promoted excited states processes in which intermediate cation radical desilylation serves as the driving force are found in the photochemistry of phthalimides. 5,6 Mazzocchi et al reported that the photochemistry of Nmethylphthalimide (1) in presence of alkenes is characterized by the two competing processes 7 : In one of these reactions the alkene adds to the C(O)-N bond of N-methylphthalimide that ultimately leads to a ring expanded benzazepinedione (3).…”
Section: Introductionmentioning
confidence: 99%